Tata Kelola Program Mudik Gratis sebagai Upaya Peningkatan Kualitas Pelayanan Transportasi Publik di Sulawesi Tenggara - Muhamad Rajulan; Maudhy Satyadharma; Hado; Nasrul; Sylsiani Mursalim (Jurnal Administrasi Karya Dharma, 2026)
This study aims to analyze the influence of the governance of the free homecoming program on the quality of public transportation services in Southeast Sulawesi Province. The study used a quantitative approach with descriptive methods and simple linear regression analysis. The sample consisted of 99 respondents who were users of the free homecoming service in 2026. The results showed that governance had a positive and significant effect on service quality, with a regression coefficient of 0.964 and a determination value of 60.7%. This indicates that better governance improves the quality of public transportation services. These findings emphasize the importance of transparency, accountability, and inter-agency coordination in increasing the effectiveness of the free homecoming program, thus ensuring optimal, safe, and comfortable service delivery and sustainably increasing public satisfaction.